2015
DOI: 10.3892/ol.2015.3725
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the IGF-II/IGF-1R axis and inhibition of IGFBP-3 by miR-155 in hepatocellular carcinoma

Abstract: Abstract. Hepatocellular carcinoma (HCC) is characterized by the aberrant expression of a number of genes that govern crucial signaling pathways. The insulin-like growth factor (IGF) axis is important in this context, and the precise regulation of expression of members of this axis is known to be lost in HCC. miR-155 is a well-established oncogene in numerous types of cancer. However, to the best of our knowledge, its effect on the regulation of the IGF axis has not been investigated to date. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Then, dual-luciferase reporter assay also determined that IGFBP3 was a target mRNA of miR-409-3p in OS. Interestingly, previous studies determined that IGFBP3 was a target mRNA of miR-196b, miR-1290, miR-384, miR-34/449 and miR-155 in cancers [ 37 40 ], but the regulatory mechanism of miR-409-3p/IGFBP3 has not been verified in OS. Accumulating researches indicated that IGFBP3 played an important role in regulating cell cycle and apoptosis in various cancers, including breast cancer, nasopharyngeal carcinoma, OS, etcetera [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, dual-luciferase reporter assay also determined that IGFBP3 was a target mRNA of miR-409-3p in OS. Interestingly, previous studies determined that IGFBP3 was a target mRNA of miR-196b, miR-1290, miR-384, miR-34/449 and miR-155 in cancers [ 37 40 ], but the regulatory mechanism of miR-409-3p/IGFBP3 has not been verified in OS. Accumulating researches indicated that IGFBP3 played an important role in regulating cell cycle and apoptosis in various cancers, including breast cancer, nasopharyngeal carcinoma, OS, etcetera [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other than methylation and proteolysis, miRNA regulation may be another mode for IGFBP3 inactivation. For example, miR-21 enhances glioblastoma tumorigenesis by downregulating IGFBP3 (29); onco-miRs miR-155 and miR-125b also target IGFBP3, promoting migration and invasion in HCC and NSCLC through the IGF-II/IGF-1R axis (30) and downstream PI3K/AKT activation (31). miRNAs regulate complementary mRNAs by inducing translational suppression and mRNA destablization.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the molecular mechanisms by which miR-let-7a performs its tumor-suppressive function in HCC, we intended to define networks of miR-let-7a targets, which might be involved in the regulation of tumor-relevant pathways. Since we are mainly interested in the IGF signaling pathway and its role in hepatocarcinogenesis (El Tayebi et al, 2011, 2015; Assal et al, 2015; Fawzy et al, 2016; Habashy et al, 2016; Youness et al, 2016; Rahmoon et al, 2017), we selected IGF-axis members potentially targeted by miR-let-7a using in silico microRNA target prediction softwares. This analysis yielded IGFII, IGF2BP2 as well as IGF2BP3 as potential miR-let-7a targets (Figure 2).…”
Section: Resultsmentioning
confidence: 99%